Criticism of the Technocratic Paradigm (Cultura Económica, 2019)
The essay analyses chapter III of the Encyclical Letter Laudato Si’, which focuses on the change of the cultural paradigm generated by digital revolution of recent decades. Throughout the text, the author reflects on the current situation and anticipates the possible problems that technocracy will entail for the human being and society.
Keywords: LAUDATO SI'; CULTURE; TECHNOCRACY; TRANSHUMANISM; GLOBALIZATION